PENDIDIKAN KARAKTER ANAK USIA SEKOLAH DASAR PENDIDIKAN KARAKTER ANAK USIA SEKOLAH DASAR PENDIDIKAN KARAKTER ANAK USIA SEKOLAH DASAR PENDIDIKAN KARAKTER ANAK USIA SEKOLAH DASAR PENDIDIKAN KARAKTER ANAK USIA SEKOLAH DASAR PENDIDIKAN KARAKTER ANAK USIA SEKOL - Simbolon, Erikson (IN VERITATE LUX, 2020)
The aim of writing this research is to determine the concept of character education and the implementation of character education for elementary school age children in the family. The location of this research is the Santa Elisabeth Tanjung Selamat neighborhood with ten families as informants. The selection of informants was carried out using purposive sampling and snowball sampling techniques. The method used in this writing is qualitative. The findings of this research show that families have implemented character education for children in the family which is implemented in everyday life. The form of implementing character education is carried out by parents by teaching children to be polite, friendly, responsible, and independent in everyday life. To educate children about life, every Sunday they join their parents in celebrating the Eucharist and also during Lent, Easter and Christmas.